Perancangan Sistem Kas Kecil Dengan Framework Codeigniter di STMIK Bani Saleh - Rina Fitriani; Dewi Prihantini; Adhitya Ilham Ramdhani; Marhakim Marhakim; Satria Satria (Journal of Digital Literacy and Volunteering, 2026)
Petty cash reporting is still done manually using Microsoft Excel. Problems often occur such as late payments, errors in calculations, physical documents causing difficulties in data retrieval and potentially resulting in lost and damaged documents. The purpose of this research is to design a Petty Cash System to provide fast, timely and accountable financial reports. The research method is Research & Development (R&D) and the establishment of the Petty Cash Imprest Fund System. This system is made web-based and uses the Codeigniter framework. The results of the study show that the petty cash information system is useful in managing petty cash more effectively, accurately, safely, and efficiently in the financial administration process, as well as minimizing the potential for errors and data loss in petty cash reporting.